(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic is related to an acute respiratory disease caused by the new coronavirus (SARS-Cov-2), an evolution still little known. The current recommendations, regarding breastfeeding, is the maintenance of breastfeeding, even for mothers who present suspicion or confirmation of COVID-19. Objective to evaluate the repercussions of the COVID-19 pandemic on the relationship between mothers and breastfeeding. Method: This is a cross-sectional, exploratory, descriptive study with a quantitative approach, conducted at the Liberdade Family Health Unit, located in the city of Tracunhaém, in the Zone of North Forest of Pernambuco. The sample was composed of 78 postpartum women who participated in prenatal consultations in the unit, and who wanted to participate in the research, while data collection was carried out in the period from August to September 2021. Results and discussion: The survey, initially, had 92 (100%) postpartum women whose contact was provided by the analyzed FHU, of which 14 (15%) were not available to participate in the survey and/or did not answer the phone calls or changed their number, totaling 78 postpartum women (100%) participants. Conclusion: In relation to the data discussed, it was observed that the majority of postpartum women did not receive guidance regarding care during breastfeeding, thus increasing the risk of contamination of the child.